A Case of Cutaneous Inflammatory Myofibroblastic Tumor. Issue 6 (22nd September 2016) - de Menezes, Sara; Mar, Adrian; Dowling, John; Wright, Annaliesa
Abstract: Inflammatory myofibroblastic tumor (IMT) rarely occurs as a primary cutaneous lesion. We report a case of cutaneous IMT in an 8‐year‐old girl presenting with an ulcerated nodule on the cheek. Although cutaneous IMT poses a diagnostic challenge because of its rarity, excision of the lesion is likely to be curative.